Legal Review of Legal Protection for Motorcycle Owners in Cases of Embezzlement and the Responsibility of Related Parties - Alfathin Zakiy; Syahranuddin Syahranuddin; Rahul Ardian Fikri (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study analyzes the legal review of legal protection for motorcycle owners in cases of embezzlement. To anticipate the development of society in relation to changes in crime, efforts can be made to plan the creation of criminal law that accommodates all the dynamics of society. This is a policy issue, namely regarding the selection of means in regulating social life. The crime of theft is regulated in the Criminal Code book II chapter XXII Articles 362 to Article 367. Indonesia is a country that is included in the category of developing countries and of course cannot be separated from the problems that have been raised above. Crimes that occur in developing countries are still relatively high. Therefore, it is not surprising that the problem of crime or criminality in Indonesia is a result of the life of its people. Crime can be interpreted criminologically and juridically. One example of a crime is the crime of embezzlement which is regulated in Articles 372 to 377 of the Criminal Code. The normative juridical research method with a descriptive approach, this study reveals that legal protection for motorcycle owners in embezzlement cases is based on Article 372 of the Criminal Code and Law Number 8 of 1981 concerning Criminal Procedure Law. The concept of imposing criminal penalties on embezzlement crimes in Indonesia. Article 372 of the Criminal Code and Law Number 8 of 1981 concerning Criminal Procedure Law. Thus, the judge sentenced the defendant to 3 (three) years in prison.